Analysis Of Mental Workload With NASA- TLX Method On Employees Of Kareb Bojonegoro Cooperative - Aditiya Anggara Putra; Rio Chandra Pratama; Ardana Putri Farahdiansari (Journal of Information System, Technology and Engineering, 2023)
The human body is designed to perform daily work activities that allow humans to be able to move the body and perform. The presence of muscle mass whose weight is almost more than half the weight of the body, allows us to be able to move and do work. NASA – TLX is a widely used assessment tool, at the time of assessing perceived workload to assess the effectiveness of tasks, systems, or teams or other aspects of performance. This method is in the form of a questionnaire developed based on subjective measurement needs that are easier but more sensitive to workload measurement. Based on the calculation results in table 5 on employees of the KAREB Bojonegoro Cooperative outlet, it can be seen that the highest NASA-TLX score was obtained by respondents with the initials WA with a score of 82, while the lowest score was obtained by respondents with the initials MR with a score of 41.33. Based on the results of determining the category, it can be seen that as many as 1 respondent is categorized as having a very high workload, while 14 respondents are categorized as having a high workload, while 10 respondents are categorized as having a medium workload. The age attribute consists of 7 respondents aged 17 – 25 years, 14 respondents aged 25 – 40 years, 4 respondents aged 41 – 55 years. From the results